Osseous Metaplasia of the Cervix: A Rare Transformation Can Mimic a Tumor—Literature Review - Ameerah Alsaqobi; Nabeel Al-Brahim (Case Reports in Pathology)
Background. The transformation of nonosseous soft tissue into bone is known as osseous metaplasia (OM). This condition most commonly affects the musculoskeletal and central nervous systems and it is a well-known phenomenon in different soft tissue organs. Rarely, OM can affect the uterus, which can extend into the cervix. OM affecting the cervix alone is a more rare condition that has multiple different clinical presentations. The presentation can be similar to that of a tumor in extremely rare cases. Case Summary. A 23-year-old nulligravida was complaining of irregular vaginal bleeding for one-month duration. Speculum examination revealed a foul-smelling bloody purulent discharge, tender cervix, and a brownish growth located at the posterior cervical lip. A punch biopsy of the growth was performed. Histological examination of the tissue revealed multiple bone fragments with necrosis and an inflammatory exudate. Because of the unusual findings, a repeat biopsy was performed. The biopsy yielded the same findings, which confirmed the diagnosis of osseous metaplasia of the cervix. Conclusion. Although osseous metaplasia is a known phenomenon in different soft tissues, it is extremely rare in the uterine cervix and can mimic malignancy. Therefore, clinicians should be aware of it.